Clinical relevance of Staphylococcus saccharolyticus detection in human samples: a retrospective cohort study - Michels, Ricarda; Papan, Cihan; Boutin, Sébastien; Alhussein, Farah; Becker, Sören L.; Nurjadi, Dennis; Last, Katharina (Infection, 2025)
Purpose: To characterize the clinical relevance of S. saccharolyticus and to identify criteria to distinguish between infection and contamination. Methods: We retrospectively investigated clinical features of patients with S. saccharolyticus detection between June 2009 and July 2021. Based on six criteria, infection was considered likely for patients with a score from 3 to 6 points, infection was considered unlikely for patients with a score from 0 to 2 points. We performed group comparison and logistic regression to identify factors than are associated with likely infection. In addition, whole genome sequencing (WGS) of 22 isolates was performed. Results: Of 93 patients in total, 44 were assigned to the group “infection likely” and 49 to the group “infection unlikely”. Multiple regression analysis revealed “maximum body temperature during hospital stay” to have the strongest predictive effect on likely infection (adjusted odds ratio 4.40, 95% confidence interval 2.07–9.23). WGS revealed two different clades. Compared to isolates from clade A, isolates from clade B were more frequently associated with implanted medical devices (3/10 vs. 9/12, p = 0.046) and a shorter time to positivity (TTP) (4.5 vs. 3, p = 0.016). Both clades did neither differ significantly in terms of causing a likely infection (clade A 7/10 vs. clade B 5/12, p = 0.23) nor in median length of hospital stay (28 vs. 15.5 days, p = 0.083) and length of stay at the ICU (21 vs. 3.5 days, p = 0.14). Conclusion: These findings indicate that S. saccharolyticus can cause clinically relevant infections. Differentiation between infection and contamination remains challenging.